2008
DOI: 10.1259/bjr/90916004
|View full text |Cite
|
Sign up to set email alerts
|

Trends in compressed breast thickness and radiation dose in breast screening mammography

Abstract: An analysis was performed of the compressed breast thickness recorded in 146 mammographic patient dose surveys each consisting of 50 or more women carried out between 1993 and 2004. The results show a steady and statistically significant increase in compressed breast thickness with time, which is also present when individual independent screening centres and equipment manufacturers are compared. This increase seems most likely to be associated with an increase in the proportion of women in the breast screening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 7 publications
3
11
0
Order By: Relevance
“…For example, Young et al [22] found an average compressed breast thickness of 56.8 mm and 54.1 mm for oblique and craniocaudal views, respectively, and Hendrick et al [23] recorded a mean compressed breast thickness of 54 mm. A more recent study by Robinson and Kotre [25] found an average compressed breast thickness of 60 mm which is comparable to this study. Robinson and Kotre [25] explained the increase in compressed breast thickness since the earlier surveys as due to an associated increase in the proportion of women in the breast screening age range classified as overweight and obese.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…For example, Young et al [22] found an average compressed breast thickness of 56.8 mm and 54.1 mm for oblique and craniocaudal views, respectively, and Hendrick et al [23] recorded a mean compressed breast thickness of 54 mm. A more recent study by Robinson and Kotre [25] found an average compressed breast thickness of 60 mm which is comparable to this study. Robinson and Kotre [25] explained the increase in compressed breast thickness since the earlier surveys as due to an associated increase in the proportion of women in the breast screening age range classified as overweight and obese.…”
Section: Discussionsupporting
confidence: 90%
“…A more recent study by Robinson and Kotre [25] found an average compressed breast thickness of 60 mm which is comparable to this study. Robinson and Kotre [25] explained the increase in compressed breast thickness since the earlier surveys as due to an associated increase in the proportion of women in the breast screening age range classified as overweight and obese. Robinson and Kotre [25] did not completely eliminate changes in equipment design and differences between different models as a cause of an overall upward trend.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A similar positive correlation between MGD and CBT was noted on a much smaller sample of Bosnian patients (Kunosic et al, 2010). An influence of CBT on patient doses during mammographic diagnostic examinations was confirmed by other authors in their researches (Wall & Roberts, 1992;Gentry & De Werd, 1996;Dance et al, 2000;Kruger et al, 2001;Oh et al, 2003;Bouzarjomehri et al, 2006;Sookpeng & Ketted, 2006;Bor et al, 2008;Robinson & Kotre, 2008) and some authors used this dependency to predict patient doses through training of artificial neural networks (Ceke et al, 2009). The number of previously conducted mammographic examinations for the complete group was 1,80 (SD: 0,66) while more than 75 % of patients underwent at least 2 mammographic examinations in their lives.…”
Section: Patient's Dosesmentioning
confidence: 69%
“…34,35 Each phantom was 6 cm in height, comparable to average compressed breast thickness during mammography. 36 The phantoms were composed of two sections-the first being a 5 cm lower slab, and the second being a 1 cm thick upper slab (placed on top of the lower section). The two-section design facilitated the addition of internal inclusions with different contrasts created by mixing intralipid with varying amounts of blood.…”
Section: Iid Phantom Imagingmentioning
confidence: 99%